2015
DOI: 10.1073/pnas.1520883112
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic CRISPR RNA-Cas9–guided genome editing in human cells

Abstract: Genome editing with the clustered, regularly interspaced, short palindromic repeats (CRISPR)-Cas9 nuclease system is a powerful technology for manipulating genomes, including introduction of gene disruptions or corrections. Here we develop a chemically modified, 29-nucleotide synthetic CRISPR RNA (scrRNA), which in combination with unmodified transactivating crRNA (tracrRNA) is shown to functionally replace the natural guide RNA in the CRISPR-Cas9 nuclease system and to mediate efficient genome editing in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(194 citation statements)
references
References 52 publications
2
183
0
Order By: Relevance
“…1 and 2). This is consistent with previously studies reporting that the seed region is sensitive to chemical modifications 23 . In our recent study, we demonstrated that by using the structure of Cas9–sgRNA as a guide, sgRNA and crRNA can be chemically modified to enhance their activity in cells and animals 34 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…1 and 2). This is consistent with previously studies reporting that the seed region is sensitive to chemical modifications 23 . In our recent study, we demonstrated that by using the structure of Cas9–sgRNA as a guide, sgRNA and crRNA can be chemically modified to enhance their activity in cells and animals 34 .…”
Section: Discussionsupporting
confidence: 94%
“…21). Chemically modified crRNA and sgRNA have been developed to enhance efficiency in cells 22,23 . However, use of chemical modification to reduce off-target effects has not been demonstrated.…”
mentioning
confidence: 99%
“…Several protocols for the unbiased detection of genome-wide Cas9 off-target activity in cells have been recently described (Frock et al, 2015; Kim et al, 2015; Ran et al, 2015; Tsai et al, 2015; Wang et al, 2015), and are important complements to biased off-target detection methods based on in silico prediction and targeted sequencing (Fu et al, 2013; Hsu et al, 2013; Mali et al, 2013a; Pattanayak et al, 2013) (see ‘Unbiased genome-wide off-target detection’ ). The adoption of these protocols marks an important departure from standardized methods of measuring an inherently biased subset of potential off-target sites.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleofection or transient transfection ) of a preformed Cas9 ribonucleoprotein complex has also been shown to reduce offtarget effects, enabling DNA-free gene editing in primary human T cells (Schumann et al 2015), embryonic stem cells (Liu et al 2015b), Caenorhabditis elegans gonads (Paix et al 2015), mouse (Menoret et al 2015;Wang et al 2015a) and zebrafish embryos , and even plant protoplasts (Woo et al 2015). The incorporation of specific chemical modifications known to protect RNA from nuclease degradation and stabilize secondary structure can further enhance Cas9 ribonucleoprotein activity (Hendel et al 2015;Rahdar et al 2015). In a clever marriage of genome-editing platforms, the FokI cleavage domain has even been fused to an inactivated Cas9 variant to generate hybrid nucleases that require protein dimerization for DNA cleavage (Guilinger et al 2014b;Tsai et al 2014), theoretically increasing CRISPRCas9 specificity.…”
Section: Crispr-cas9mentioning
confidence: 99%